2015
DOI: 10.1097/fjc.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Selective Heart Rate Reduction Improves Metabolic Syndrome–related Left Ventricular Diastolic Dysfunction

Abstract: In rats with MS, HRR induced by the If inhibitor S38844 improved LV diastolic function and endothelium-dependent vascular dilatation, independent from modifications in metabolic status. Moreover, this improvement in cardiac function involves not only immediate effects such as improved myocardial perfusion and reduced oxidative stress but also long-term effects such as modifications in the myocardial structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…Furthermore, improved NO bio‐availability in the coronary vasculature may contribute, via improved coronary endothelial function, to the improvement of LV diastolic dysfunction. Indeed, the increase in myocardial tissue perfusion observed after finerenone treatment reported in the present study suggests improved coronary endothelial function, and the association between increased coronary endothelial NO bio‐availability and improved myocardial perfusion has been reported in this model with other drugs such as β‐blockers and If current inhibitors . The normalization of myocardial perfusion by finerenone probably prevents the LV tissue hypoxia observed in Zucker fa/fa rats and subsequent activation of mechanisms inducing LV dysfunction.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Furthermore, improved NO bio‐availability in the coronary vasculature may contribute, via improved coronary endothelial function, to the improvement of LV diastolic dysfunction. Indeed, the increase in myocardial tissue perfusion observed after finerenone treatment reported in the present study suggests improved coronary endothelial function, and the association between increased coronary endothelial NO bio‐availability and improved myocardial perfusion has been reported in this model with other drugs such as β‐blockers and If current inhibitors . The normalization of myocardial perfusion by finerenone probably prevents the LV tissue hypoxia observed in Zucker fa/fa rats and subsequent activation of mechanisms inducing LV dysfunction.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, LV diastolic dysfunction was associated with LV remodelling, as illustrated by the significant increase in interstitial LV collagen density. In addition to LV diastolic dysfunction, the reduction in plasma nitrite levels, a marker of NO bio‐availability, suggests an impaired endothelium‐dependent vascular dilator response in both 13‐ and 24‐week‐old untreated Zucker fa/fa rats, illustrating that, as observed in humans with metabolic syndrome, a marked vascular endothelial dysfunction develops in this model of metabolic syndrome. The reduction of NO bio‐availability, probably attributable to an increased “NO neutralization” by the enhanced ROS production, involving, at least in part, an imbalance between the eNOS to iNOS ratio, as already recently described by Toblli et al, as well as increased levels of the endogenous NOS inhibitor asymmetric dimethyl arginine, contributes not only to vascular endothelial dysfunction but also to LV diastolic cardiac dysfunction …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this regard, previous studies using highsucrose diets have shown marked glucose intolerance in experimental animals (Brenner et al 2003;Sumiyoshi et al 2006), which is supported due to previously shown data on an association with promotion of insulin signaling and high H 2 O 2 giving a fact on typical metabolic actions of insulin linking to ROS and insulin relation (Czech et al 1974). It seems that oxidation-induced disruption of cellular redistributed signaling molecules in response to insulin stimulation is associated with impaired insulin action in case of many pathological conditions such as obesity The clustering of metabolic abnormality is closely related to the progression of cardiovascular disorders (Balderas-Villalobos et al 2013;Merabet et al 2015;Okatan et al 2016). Indeed, a correlation between obesity, insulin resistance and contractile dyfunction at most due to defect in intracellular Ca 2+ handling in rat heart with MetS have been observed, previously (Balderas-Villalobos et al 2013;Nevelsteen et al 2013).…”
Section: R a F Tsupporting
confidence: 61%
“…ECG is one of the standard technologies used to monitor and assess cardiac function, and provide insight into the mechanisms driving myocardial pathology. In the present study, we evaluated in situ ECG in rats with MetS and showed that there is significantly decreased QRS amplitude and shortened QT-interval together with markedly increased heart rate, similar to previously mentioned for both animals and humans (Korkmaz-Icoz et al 2016;Merabet et al 2015;Okatan et al 2015). It is accepted that increased heart rate observed in MetS contributes to the deterioration of LV function via impaired LV filling and relaxation, reduced coronary perfusion and cardiac output.…”
Section: R a F Tmentioning
confidence: 81%